Morphological variation of the kidneys with its pathological relevance - K Anupama; Shameem Shariff; Shailaja Shetty (Wolters Kluwer Medknow Publications, 2016)
Kidneys are bean shaped organs with the length of 1 lcms, breadth of 6cms and thickness of 3cms in anteroposterior dimension. Variations in morphology of the kidneys are either congenital or acquired. The present paper deals with two cases with abnormal morphology. During routine dissection of abdomen for the under graduate students in MVJ Medical College, Bengaluru, it was found that there were kidneys with morphological variations in two cadavers. Both these specimens were analysed morphologically and sent for histopathological examination. The specimen No: 1 was a case of Ask Upmark kidney and Specimen No: 2 was a case of Granular contracted kidney. Morphological changes in kidney could be congenital or acquired. It is usually associated with various pathologies of kidneys. The pathogenesis is controversial attributed to vesicoureteric reflux with intrarenal reflux or localised developmental arrest, arteriolar nephrosclerosis and glomerulonephritis. The morphology and histopathology of the cases have been discussed.